Biogas production from beverage factory wastewater in a mobile bioenergy station. (February 2021) - Lin, Chiu-Yue; Lay, Chyi-How; Chew, Kit Wayne; Nomanbhay, Saifuddin; Gu, Rui-Lin; Chang, Shen-Ho; Kumar, Gopalakrishnan; Show, Pau Loke
Abstract: Recently, the production of renewable biogas such as biohydrogen and biomethane from wastewaters through anaerobic fermentation has gained worldwide attention. In the present study, a mobile bioenergy generation station had been constructed based on a high-efficiency hydrogenesis & methanogenesis technology (HyMeTek) developed by Feng Chia University, Taiwan. The substrate was a beverage wastewater having chemical oxygen demand (COD) concentration of 1200 mg/L. This bioenergy station had a feedstock tank (3.8 m 3 ), a nutrient tank (0.8 m 3 ), an acidogenesis tank (AT, 2 m 3 ), two methanogenesis tanks (MT, 4 m 3 for each), a membrane bioreactor and a control room. Biogas production rate, methane concentration, COD removal efficiencies, energy efficiency and economical interest of the plant were assessed. The peak total methane production rates for AT (at hydraulic retention time, HRT, 4 h) and MT (at HRT 8 h) were 430 and 7 mL/L·d, respectively. A strategy of shortening HRT was a promising method to enhance biogas quality and energy efficiency. This mobile bioenergy system has commercial potential because it could bring good economic benefit of initial rate of return (58.84%) and payback time (2.68 y). Highlights: Highly efficient hydrogenesis and methanogenesis technology (HyMeTek) developed. HyMeTek as a basis for the construction of mobile bioenergy generation station. Shortened hydraulic retention time strategy enhanced the biogas production efficiency. Positive economic and energy gain using two-phase anaerobic fermentation system.